Energy Efficient Based Channel Assignment Game Algorithm for Wireless Sensor Network - Hao, Xiao-Chen; Ru, Xiao-Yue; Li, Xi-Da; Xin, Min-Jie (Wireless personal communications, 2015)
In wireless sensor network, communication interference problem is serious due to the widespread use of wireless sensor network. Meanwhile, the network may perform abnormally for the low energy node failure. The energy consumption of data retransmission is the main reason for node failure. The data retransmission is caused by communication interference. As we all know, the multi-channel technology is an effective way to alleviate the interference among nodes by using the available channel resource reasonably. The existing algorithms have higher complexity, because they assign channel for link through respectively determining the receiving and sending channel of two nodes on the link. However, the sensor node’s energy and the ability of computing access are limited greatly. Thus, it makes the solution of channel allocation problem for WSN a new challenge. To effectively solve the problem, a multiple channels allocation game model is established. It considers the influence of node energy to avoid the extra energy consumption with effect. And, the path gain is introduced to accurately describe the interference. Furthermore, a kind of Energy Efficiency based multiple channels allocation algorithm is proposed in this paper. In addition, the algorithm only assigns receiving channel for sensor node to avoid the high complexity of algorithm. And it combines dynamic channel switching to complete channel adjustment in communication. The analysis results demonstrate that the channel allocation game is a potential game and it can converge to the state of Nash equilibrium. The simulation results show that the algorithm can greatly decrease the convergence round, effectively reduce the interference of low-energy nodes and improve the anti-jamming network performance.